2014
DOI: 10.1159/000360134
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variety in Electrolyte Levels and Prevalence of Dysnatremias and Dyskalemias in Patients Presenting to the Emergency Department

Abstract: Background: It was found that age and female gender are predisposing factors for hyponatremia in patients taking thiazides. Objective: To investigate whether a relationship exists between age and gender and serum sodium and potassium as well as the prevalence rates in a large population of patients presenting to the emergency department of a university hospital. Methods: In this retrospective analysis we gathered data on age, gender and current diuretic medication of all patients admitted to the emergency depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 14 publications
7
35
0
1
Order By: Relevance
“…Die Prävalenz ist maßgeblich vom Alter abhängig. So stieg sie in einer Untersuchung im Notaufnahmekollektiv von 2,3% bei 16-bis 21-Jährigen auf 16,9% bei über 80-Jährigen [4]. Ältere Frauen sind deutlich häufiger betroffen als ältere Männer.…”
Section: Hyponatriämieunclassified
“…Die Prävalenz ist maßgeblich vom Alter abhängig. So stieg sie in einer Untersuchung im Notaufnahmekollektiv von 2,3% bei 16-bis 21-Jährigen auf 16,9% bei über 80-Jährigen [4]. Ältere Frauen sind deutlich häufiger betroffen als ältere Männer.…”
Section: Hyponatriämieunclassified
“…But electrolytes in our skin, bones, internal organs, and muscles are actually decreasing. 27) This is similar to energy consumption by a battery, and although the voltage drop is not obvious, the electrolyte depletion is. Heart failure is a kind of self-increasing disease, or in other words, the heart function of patients with heart failure becomes more and more serious with age.…”
Section: Discussionmentioning
confidence: 85%
“…Considering that we have chosen the threshold of 136 mmol/L for defining moderate hyponatremia, as suggested by Adrogué and Madias [1], it is predictable that the frequency of this condition would be substantially reduced using lower cut-offs (i.e., 12.3%, 8.7% and 2.6% using serum sodium values < 135 mmol/L, < 134 mmol/L and < 130 mmol/L, respectively), but still remaining higher than that reported in previous studies [5][6][7][8][9]. The prevalence of hyponatremia in ED patients was also found to be approximately 5-time higher than that observed in unselected outpatients of the same geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…Assen et al performed a retrospective observational study including over 10,600 patients admitted to the ED over a 10-month period [8], and found hyponatremia (serum sodium < 130 mmol/L) in 2.4% of patients. More recently, Lindner reviewed data of all patients admitted to the emergency department of a large university hospital over a 2-year period (n = 20,667) [9], and concluded that the prevalence of hyponatremia increased from 2.3% in patients aged 16-21 years up to 16.9% in those aged > 80 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation